Discrimination of FCGR2B polymorphism without coamplification of FCGR2A and FCGR2C genes. (11th December 2017) - Bonatti, F.; Adorni, A.; Percesepe, A.; Martorana, D.
Summary: The FCGR locus is characterized by high polymorphism and sequence homology. In particular, the Ile232Thr polymorphism in the FCGR2B gene results in inaccurate genotyping in most published papers. The purpose of the study was to develop an accurate genotyping assay able to discriminate this polymorphism.